Biosynthesis of Silver Nanoparticles by Pseudomonas aeruginosa and Evaluation of Their Antibacterial Activity and Cytotoxicity Assay Properties (Iraqi Journal of Medical Sciences, 2024)
Background: Utilizing Pseudomonas aeruginosa (P. aeruginosa) to biosynthesize silver nanoparticles (AgNPs). Antibiotic resistance poses a formidable challenge, particularly against multidrug-resistant (MDR) bacteria. The employment of supernatant as a cost-effective and straightforward approach enhances the efficacy of AgNPs biosynthesis.Objective: To explore the biosynthesis of AgNPs by P. aeruginosa with the aim of achieving cost-effective and environmentally friendly production methods while ensuring novel morphological characteristics of AgNPs furthermore evaluated of antimicrobial and toxicity.Methods: Preparation AgNPs by biological method (Green synthesis). Ultraviolet-visible spectrophotometer (UV–Vis), energy dispersive of X-ray spectroscopy (EDX), scanning electron microscopy (SEM), atomic force microscopic (AFM), X-ray diffraction (XRD) Zeta potential analysis. These techniques were applied for physical characterization. Disc diffusion assay and minimum inhibitory concentration (MIC) (16 ?g/ml), were evaluated against different strain of Gram negative and positive bacteria, and study cytotoxicity assay normal human dermal fibroblasts (HdFn) and cell line A549.Results: The UV–Vis showed the peak absorption at 421 nm wavelength, SEM showed nanoparticles were homogeneous and spherical shape with average size 24.5 nm and energy dispersive EDX confirmed the purity of the synthesized nanoparticle, where it was observed that the AgNPs showed strong antibacterial activity against MDR bacteria and the best MIC was 32 ?g/ml concentration and showed the best efficacy against resistant strains of Gram-positive and negative bacteria Furthermore, AgNPs did not show any cytotoxic effects on carcinoma cell line A549.Conclusion: The biological method used in this research is suitable to prepare AgNPs according to the size of particle and homogeny of the product and show strong antimicrobial property against MDR pathogens without having toxicity effect on cell line tissue.Keywords: Silver nanoparticles, Pseudomonas aeruginosa, antibacterial activity, cytotoxicity, biomedical applicationsCitation: Huseen DA, Ahmed ME, Hamid MK. Biosynthesis of silver nanoparticles by Pseudomonas aeruginosa and evaluation of their antibacterial activity and cytotoxicity assay properties. Iraqi JMS. 2024; 22(1): 154-163. doi: 10.22578/IJMS.22.1.17
Keywords: Silver nanoparticles; Pseudomonas aeruginosa; antibacterial activity; cytotoxicity; biomedical applications